Research Progress on Na3V2(PO4)3 Cathode Material of Sodium Ion Battery - Zeng, Xianguang; Peng, Jing; Guo, Yi; Zhu, Huafeng; Huang, Xi (Frontiers in Chemistry, 2020)
Sodium ion batteries (SIBs) are one of the most potential alternative rechargeable batteries because their low cost, high energy density, high thermal stability and good structure stability. The cathode materials play a crucial role in the cycling life and safety of SIBs. Among reported cathode candidates, Na3V2(PO4)3 (NVP), a representative electrode material for sodium super ion conductor based, has good application prospects due to its good structural stability, high ion conductivity and high platform voltage ( 3.4 V). However, its practical applications are restricted by comparatively low electronic conductivity. In this review, recent progresses of Na3V2(PO4)3 are well summarized and discussed, including preparation and modification methods, electrochemical properties. Looking forward to the future research and further development of Na3V2(PO4)3 cathode is also discussed.